2016
DOI: 10.1007/s00330-016-4354-y
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endovascular management of chronic superior vena cava syndrome of benign causes : long-term follow-up

Abstract: • Malposition of indwelling central catheter can cause superior vena cava obstruction. • Image-guided catheter placement helps prevent superior vena cava obstruction. • Imaging and superior vena cava obstruction classification allows adequate procedure planning. • Endovascular techniques are safe and effective for superior vena cava syndrome treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 41 publications
1
44
0
3
Order By: Relevance
“…3,4) For patients without a fistula, recurrence free survival with endovascular intervention was 91% at 1 year and 73% at 3 years. 5) Assisted patency of the SVC system was 100% at 1 and 3 years. 5) Furthermore, in our case, the failure of the Denver catheter was caused by both SVC thrombosis and intracatheter thrombosis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…3,4) For patients without a fistula, recurrence free survival with endovascular intervention was 91% at 1 year and 73% at 3 years. 5) Assisted patency of the SVC system was 100% at 1 and 3 years. 5) Furthermore, in our case, the failure of the Denver catheter was caused by both SVC thrombosis and intracatheter thrombosis.…”
Section: Discussionmentioning
confidence: 96%
“…5) Assisted patency of the SVC system was 100% at 1 and 3 years. 5) Furthermore, in our case, the failure of the Denver catheter was caused by both SVC thrombosis and intracatheter thrombosis. Although in the past, surgical removal and replacement were needed in this situation, the endovascular intervention we performed (intra-catheter balloon dilations and a Fogarty-like procedure) was also effective in eliminating the intra-catheter thrombosis and in completing immediate recanalization with good results.…”
Section: Discussionmentioning
confidence: 96%
“…An attempt at endovascular treatment of intracranial hypertension resulting from stenosis or occlusion of the venous system was based on widely available publications regarding the efficacy of such treatment strategies. [1][2][3][4] Because no clear recommendations are available regarding covered and uncovered stent placement, we decided to insert an uncovered Zilver Vena, a dedicated venous stent, at the SVC recanalization site. Although Haddad et al 5 suggested higher effectiveness of covered stents, they also emphasized the need for further studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…For recanalization of mature thrombus or nonthrombotic obstruction, less invasive methods (eg, softer guide wires and dilators, noncompliant angioplasty balloons) should be attempted before more aggressive techniques and devices (eg, sharp recanalization, cutting balloons, stent insertion) are employed, although risk‐benefit analysis and the experience of the procedural team will ultimately govern these decisions. Without long‐term outcomes data for venous stents in children, they should be used with caution and restraint …”
Section: Failure Points and Essential Components Of Carementioning
confidence: 99%
“…Without long-term outcomes data for venous stents in children, they should be used with caution and restraint. [141][142][143] Although evidence for high morbidity and mortality in children with venous catheter-related DVT is compelling, 8,144,145 until recently, data favoring anticoagulation for CVC-related thrombi and infection prophylaxis have been relatively weak. 146 Evidence regarding the effectiveness of a shorter duration of therapy and selective use is evolving.…”
Section: Catheter-related Thrombosis and Venous Obstructionmentioning
confidence: 99%